Impact of The Covid-19 Pandemic on The Psychological Response of Adolescents: A Literature Review - Ahmad Zainuri; Raden Endro Sulistyono; Arista Maisyaroh; Primasari Mahardhika Rahmawati (Nursing and Health Sciences Journal (NHSJ), 2022)
Introduction: The covid-19 pandemic caused by the novel coronavirus (Sars cov2), is an unprecedented disease with a tremendous impact on all of humanity, with long-term consequences that still need to be uncovered. This virus spread rapidly and globally in a very short time causing panic and resulted in restrictions imposed by public health authorities in many countries of the world, including travel bans, limiting social gatherings and closing public schools. The purpose of this literature review is to explore or find relationships or find out the impact of the covid-19 pandemic on adolescent psychological responses. Methods: This study uses a literature review method with article searches conducted on the Pubmed, Sciene Direct and Scopus electronic databases. There were 686 articles in the search databases Pubmed, Sciene Direct and Scopus but only 10 articles met all the inclusion criteria and were reviewed. Result: The covid-19 pandemic which is the focus of international studies (WHO) can affect the physical and mental health of a teenager. The prevalence of mental/psychological disorders in adolescents is quite high. Conclusion: Based on the results of a review of 10 literatures reviewed, based on the characteristics of respondents in the covid-19 pandemic study, there are changes in lifestyle during quarantine, have negative and potentially prolonged effects on mental health of each age in adolescents, lack of social support from parents, friends Peers and teachers at school can be at risk for their psychological disorders. There are 4 psychological symptoms, such as stress, depression, anxiety, and sleep disturbances.